2022
DOI: 10.3390/children9070977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Anemia among Adolescents Living in Hodeida, Yemen

Abstract: This study assesses the prevalence and correlates of anemia among adolescents living in the war-affected region of Hodeida in Yemen. A secondary objective was to examine the effect of a nutrition education intervention on hemoglobin levels among anemic adolescents. A cross-sectional study was conducted on a random sample of adolescents aged 15–19 years in Hodeida (n = 400). A questionnaire was administered to inquire about demographic, socioeconomic, lifestyle and clinical characteristics. Capillary blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
1
0
1
Order By: Relevance
“…this prevalence of anemia in rural area may be due to poverty and low socioeconomic status. Also similar to a study carried out in AL-Yemen (21) the prevalence of anemia in rural area was(51.3%) and in urban area was(32.2%).…”
Section: Discussionsupporting
confidence: 84%
“…this prevalence of anemia in rural area may be due to poverty and low socioeconomic status. Also similar to a study carried out in AL-Yemen (21) the prevalence of anemia in rural area was(51.3%) and in urban area was(32.2%).…”
Section: Discussionsupporting
confidence: 84%
“…Anemia lebih umum di antara mereka yang mengalami menstruasi berlebihan dengan nilai (p < 0,001), biasanya dengan gejala klinis sakit kepala, kelelahan, dan pusing (24). Hal ini sejalan dengan hasil penelitian bahwa siklus menstruasi < 21 hari berpeluang 5 kali untuk terjadi anemia (AOR 5,37, 95% CI: 2,38-9,63, nilai P = 0,013), dan siklus menstruasi 21 -25 hari berpeluang hampir 4 kali untuk terjadi anemia (AOR = 3,81, 95% CI: 1,27-5,94, nilai P=0,027) (14).…”
Section: Pembahasanunclassified
“…The results of the initial screening examination of hemoglobin levels in this study showed that as many as 33.3% of the sample suffered from anemia. Anemia in adolescence will greatly affect their health in the future (Al-Jermmy et al, 2022). The low Hb level of school children, especially at the beginning of the growth spurt, will greatly affect their growth in adolescence.…”
Section: The Effect Of Treatment On Hemoglobin Levelmentioning
confidence: 99%

Untitled

Toruntju,
Zakaria,
Roqifoh
et al. 2023
JKM